PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA BERBASIS TOLERANSI UNTUK DAERAH RAWAN KONFLIK - Muliadi, Agus; Arjun, Mursalin Arifin (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2014)
West Nusa Tenggara has been inhabited by three major tribes namely; Sasak in Lombok, Samawa, in western Sumbawa, and Mbojo tribe in the middle and east of Sumbawa Island. Other tribes in Indonesia such as Bali, Java, Medan, and others color the cultural diversity of the people of West Nusa Tenggara (NTB). The blending of various characters, cultures, and customs in a community of life is very potential to cause tribal, religious, belief, and racial conflicts. This fact occurs because of the lack of tolerance in the community. Tolerance can be built through well-planned education. This study aims to: 1) know the model of ’learning devices’ IPA based on tolerance for school / madrasah in conflict prone areas, 2) to know the ability of science teachers in applying learning tools IPA based on tolerance, 3) to know the social skills of students in science learning, 4 ) know the attitude of student’s tolerance after learning, 5) knowing student cognitive learning outcomes after science-based learning tolerance. The research used is research development with model development of Kemp et al. (1994). This research was conducted in two stages, namely: (1) Development of Learning Device which includes; (a) Instructional Problems, (b) Learner Characteristics, (c) Task Analysis, (d) Objectives, (e) Content Sequencing, (f) Instructional Strategies, (g) Instructional Delivery, (h) Evaluation Instrumens, ) Instructional Resources. (2) Testing Devices to be implemented on the students of class IX MTs Kondok Barokah Nahdlatul Wathan. Research data were analyzed using descriptive statistics by calculating descriptive statistic parameters, such as; the highest value, the lowest value, the average, standard deviation, and percentage.